Development And Implementation Of A Method Of Tension-Free Hernialloplasty Using П-Shaped Sutures For The Treatment Of Ventral Hernias In Obesity Patients - Suvonov Madaminjon Tukhtapulotovich; Shonazarov Iskandar Shonazarovich; Rakhmanov Kosim Erdanovich (International Journal of Medical Sciences And Clinical Research, 2025)
The aim of the study is to improve the results of surgical treatment of ventral hernias in obese patients by improving the technical aspects of hernialloplasty. Materials and methods of research. The study is based on clinical and laboratory examination of 121 patients with ventral hernias who were operated on in the surgical department of the Samarkand branch of the RSCEMP for the period from 2016 to 2025. Study results. The improved technique of tension-free hernialloplasty in obese patients significantly reduced the incidence of postoperative complications (8.9% vs 14.8%, p = 0.045) and completely eliminated recurrence of ventral hernias in the late period. Conclusions. The developed method of tension-free hernioalloplasty using П-shaped sutures and an "on lay" endoprosthesis significantly reduces complications and recurrences of ventral hernias in obese patients, accelerates recovery and improves clinical results.